MODEL KONSTRUK GAYA BELAJAR: STUDI PADA SEKOLAH MENENGAH KEJURUAN TEKNOLOGI INDUSTRI DI SURAKARTA - Muhammad A khyar (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2007)
This study aims at finding out the construct model of learning style. The study used the data of the second grade students of vocational high schools of Surakarta at Machinery Department that consisted ofSMK Pancasila, SMK Murni, SMK Warga, and SMK Bhineka Karya. The sample size was 291 taken by using proportional random sampling. The data collection technique used a questionaire. The data analysis technique used Confirmatory Factor Analysis. The findings of the study indicated that there were three valid indikators of learning style, namely developing creatvity (),=O,769), innovative experience (),,=0, 642), and developing skill (),=-0. 237).